Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Soil biogeochemical controls on the distribution of phosphorus fractions in the Qilian Mountains of China’s drylands - Zeng-Ru Wang; Ji-Liang Liu; Feng-Rui Li (Plant and Soil, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)